Inhibition among olfactory receptor neurons - Van der Goes van Naters, Wynand (Frontiers in Human Neuroscience, 2013)
Often assumed to be epiphenomena of a cell’s activity, extracellular currents and resulting potential changes are increasingly recognized to influence the function of other cells in the vicinity. Experimental evidence shows that even small electric fields can modulate spike timing in neurons. Moreover, when neurons are brought close together experimentally or in pathological conditions, activity in one neuron can excite its neighbors. Inhibitory ephaptic mechanisms, however, may depend on more specialized coupling among cells. Recent studies in the Drosophila olfactory system have shown that excitation of a sensory neuron can inhibit its neighbor, and it was speculated that this interaction was ephaptic. Here we give an overview of ephaptic interactions that effect changes in spike timing, excitation or inhibition in diverse systems with potential relevance to human neuroscience. We examine the mechanism of the inhibitory interaction in the Drosophila system and that of the well-studied ephaptic inhibition of the Mauthner cell in more detail. We note that both current towards and current away from the local extracellular environment of a neuron can inhibit it, but the mechanism depends on the specific architecture of each system.